1997
DOI: 10.1177/004051759706701101
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Measurement and Macroscopical Study of Sanding and Raising

Abstract: Comfort is a major selling point for clothes, and tactile comfort is essential; a fabric must be pleasant to the touch. Several textile finishing processes improve fabric touch: sanding (or emerizing) (for 30% of clothes) and raising (for polar fleece, a current popular product), for example. There is no current control system for these processes, which are very often used but not well understood. This study describes a tribological method for investigating sanding and raising, and brings to light the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 7 publications
1
30
0
2
Order By: Relevance
“…The first is a multidirectional tribometer developed by Bueno et al [3]. This device ( Figure 5) measures the friction and roughness of a fabric.…”
Section: Measurement Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is a multidirectional tribometer developed by Bueno et al [3]. This device ( Figure 5) measures the friction and roughness of a fabric.…”
Section: Measurement Methodsmentioning
confidence: 99%
“…According to the table, it is possible to define the occurrence of the four different tribologic phenomena. If a phenomenon occurs, it is noted as 1 and 0 if it does not, then the ratios are computed according to Equation 3 and put in the second line of the table. These ratios are added up for each tribologic phenomenon according to its occurrence.…”
Section: Quantifying Surface State Modification Along With the Wear Pmentioning
confidence: 99%
“…Objective fabric hand evaluation has been done using the Kawabata evaluation system (Kawabata and Niwa, 1996), a tribometer for fabrics (Bueno et al, 1997) and a thermal absorption measuring system. KES permits us to measure on fabric samples a number of mechanical features concerning tensile property, bending property, shearing property, compression property and surface property.…”
Section: Fabric Production and Evaluationmentioning
confidence: 99%
“…1996). Bueno et al. (1996, 1997) showed that calendering makes fabrics smoother and emerizing gives to fabrics little, dense and regular hairs.…”
Section: Introductionmentioning
confidence: 99%